2012
DOI: 10.1590/s1020-49892012001000004
|View full text |Cite
|
Sign up to set email alerts
|

Consumer attitudes, knowledge, and behavior related to salt consumption in sentinel countries of the Americas

Abstract: Additional effort is required to increase consumers' knowledge about the existence of a maximum limit for intake and to improve their capacity to accurately monitor and reduce their personal salt consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
49
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 13 publications
10
49
2
4
Order By: Relevance
“…Previous studies in American countries found similar findings. 9,18,19 Information concerning on appropriate understanding of recommended salt intake and the importance of salt reduction program are necessary for successful treatment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies in American countries found similar findings. 9,18,19 Information concerning on appropriate understanding of recommended salt intake and the importance of salt reduction program are necessary for successful treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study found a precise warning that indicated high or low salt content was more favorable. 9,19 Simple and clear warning of salt content will help patients in recognizing salt/sodium amount that they consume. Further, the development of clearer food labels is strongly recommended and would be helpful in salt reduction programs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations